Prevalence of pfk13 and pfmdr1 polymorphisms in Bounkiling, Southern Senegal - Ahouidi, Ambroise (2021)
BACKGROUND: Delayed Plasmodium falciparum parasite clearance has been associated with Single Nucleotide Polymorphisms (SNPs) in the kelch protein propeller domain (coded by pfk13 gene). SNPs in the Plasmodium falciparum multidrug resistance gene 1 (pfmdr1) are associated with multi-drug resistance including the combination artemether-lumefantrine. To our knowledge, this is the first work providing information on the prevalence of k13-propeller and pfmdr1 mutations from Sédhiou, a region in the south of Senegal. METHODS: 147 dried blood spots on filter papers were collected from symptomatic patients attending a hospital located in Bounkiling City, Sédhiou Region, Southern Senegal. All samples were collected between 2015-2017 during the malaria transmission season. Specific regions of the gene pfk13 and pfmdr1 were analyzed using PCR amplification and Sanger sequencing. RESULTS: The majority of parasites (92.9%) harboured the pfk13 wild type sequence and 6 samples harboured synonymous changes. Regarding pfmdr1, wild-type alleles represented the majority except at codon 184. Overall, prevalence of 86Y was 11.9%, 184F was 56.3% and 1246Y was 1.5%. The mutant allele 184F decreased from 73.7% in 2015 to 40.7% in 2017. The prevalence of haplotype NFD decreased from 71.4% in 2015 to 20.8% in 2017. CONCLUSIONS: This study provides the first description of pfk13 and pfmdr1 genes variations in Bounkiling, a city in the Sédhiou Region of Senegal, contributing to closing the gap of information on anti-malaria drug resistance molecular markers in southern Senegal.